2006
DOI: 10.1007/s00417-005-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and low plasma folate as risk factors for central retinal vein occlusion: a case–control study in a Chinese population

Abstract: The results suggest that hyperhomocysteinemia and low plasma folate are independent risk factors for CRVO and are associated with the development of CRVO in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
3
15
0
2
Order By: Relevance
“…Homocysteine was found to be elevated in various other population-based studies such as the Iranian and the Chinese. They reported it as a risk factor for CRVO 19 20. Similar to our earlier study, Latanzio et al 21 reported that homocysteine was the risk factor for early onset CRVO.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Homocysteine was found to be elevated in various other population-based studies such as the Iranian and the Chinese. They reported it as a risk factor for CRVO 19 20. Similar to our earlier study, Latanzio et al 21 reported that homocysteine was the risk factor for early onset CRVO.…”
Section: Discussionsupporting
confidence: 79%
“…Reduced folate and B 12 , apart from lowering of methionine, were seen in the Indian population in our previous study 3. Gao et al 20 identified low plasma folate as an independent risk factor for CRVO apart from hyperhomocysteinaemia, in the Chinese population.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, in our study, mean total plasma homocysteine level was significantly higher in cases, than control subjects. This was also demonstrated by Gao et al [33] in a Chinese population in which the homocysteine level is low. However, we failed to find any difference in existence of hyperhomocysteinemia among different ages, whereas other studies [15] demonstrated stronger association in patients younger than 70 years old.…”
Section: Discussionsupporting
confidence: 62%
“…Lattanzio et al [15] have reported an OR of 3.0 for fasting HHcys in patients with CRVO and an OR of 1.3 was reported by another study in a Chinese population [22]. The meta-analysis by Janssen et al [23] has also shown an overall OR of 8.9 (95 % CI, 5.7-13.7) for Hcys.…”
Section: Resultsmentioning
confidence: 93%